Power quality in the future grid - Results from CIGRE/CIRED JWG C4.24 - Zavoda, Francisc; Langella, Roberto; Lazaroiu, George C.; Bollen, Math; Ronnberg, Sarah K.; Meyer, Jan; Ciufo, Phil (2016 17th International Conference on Harmonics and Quality of Power (ICHQP), 2016)
This paper gives a status report on activities of CIGRE/CIRED JWG C4.24. The following issues are addressed in the paper: Introduction, scope of the report and terminology; New developments in power electronics (PE); Changes in probability of interference; Microgrids and PQ; Volt-VAR control and PQ; Feeder reconfiguration and PQ; Demand side management and PQ; New measurement techniques; New mitigation.